En studentfest år 1777: om maktspel, vältalighet och förlustelser i Uppsala - Burman, Lars (1700-tal: Nordic Journal for Eighteenth-Century Studies, 2011)
In 1777 new statutes were adopted at Östgöta nation, one of the mandatory student associations in Uppsala. In connection with this a lavish feast was arranged, which comprised both a dinner with invited university guests and an oration by one of the younger nation members. The orator was Carl Gustaf Leopold (1756-1829), who was later to become a member of the Swedish Academy. The article proposes that the festivities can be regarded as an attempt to further legitimize the nation organizations, and to make clear that the nations considered themselves as dependable and closely connected to the university. The consistory of the university hesitated to ratify the new statutes; the matter was not considered to be a question for the university. Östgöta nation, however, would later obtain a confirmation directly from the chancellor. The festivities were thus a symbolic manifestation and a method of persuasion. The goals and tactics can be inferred from the nation’s memoranda books, but also from Leopold’s oration. The article contains a rhetorical analysis of his argumentation. A facetious poem by the young docent Eric Michael Fant (1754-1817), who depicted the event and the ensuing revelries, throws light on the occasion. A complete transcription of the manuscript is included.